The player surface interaction of rugby players with 3G artificial turf during rugby specific movements - Ferrandino, M.; Forrester, S.; Fleming, P. (Procedia Engineering, 2015)
A number of high profile rugby teams in the UK have installed ATS for both training and competition. However, little is known about how the player interacts with ATS during rugby specific tasks. To date the pitches are tested using mechanical testing devices with little understanding as to how these relate to the player interaction with the surface. The aim of this pilot study was to determine the viability of using 3D motion capture system to quantify the player surface interaction and surface performance characteristics during rugby specific movements. Two tasks were selected, kicking and simulated scrummaging, for players to perform on a sample ATS within a biomechanics laboratory. Using a 3D motion capture system synchronised with a force plate the movement of the players on the ATS was analysed. This analysis showed that using a 3D motion capture system with players on an ATS was a viable method to investigate and understand the interaction between the player and the surface. Baseline data for comparison between player loading and the mechanical testing devices was also obtained.